Disease burden and economic impact of diagnosed non‐alcoholic steatohepatitis in five European countries in 2018: A cost‐of‐illness analysis. (18th March 2021) - Schattenberg, Jörn M.; Lazarus, Jeffrey V.; Newsome, Philip N.; Serfaty, Lawrence; Aghemo, Alessio; Augustin, Salvador; Tsochatzis, Emmanuel; de Ledinghen, Victor; Bugianesi, Elisabetta; Romero‐Gomez, Manuel; Bantel, Heike; Ryder, Stephen D.; et al.
Abstract: Background and aims: Non‐alcoholic steatohepatitis (NASH) is a chronic disease that can progress to end‐stage liver disease (ESLD). A large proportion of early‐stage NASH patients remain undiagnosed compared to those with advanced fibrosis, who are more likely to receive disease management interventions. This study estimated the disease burden and economic impact of diagnosed NASH in the adult population of France, Germany, Italy, Spain and the United Kingdom in 2018. Methods: The socioeconomic burden of diagnosed NASH was estimated using cost‐of‐illness methodology applying a prevalence approach to estimate the number of adults with NASH and the attributable economic and wellbeing costs. Given undiagnosed patients do not incur costs in the study, the probability of diagnosis is central to cost estimation. The analysis was based on a literature review, databases and consultation with clinical experts, economists and patient groups. Results: The proportion of adult NASH patients with a diagnosis ranged from 11.9% to 12.7% across countries, which increased to 38.8%‐39.1% for advanced fibrosis (F3‐F4 compensated cirrhosis). Total economic costs were €8548‐19 546M. Of these, health system costs were €619‐1292M. Total wellbeing costs were €41 536‐90 379M. The majority of the undiagnosed population (87.3%‐88.2% of total prevalence) was found to have early‐stage NASH, which, left untreated, may progress to more resource consuming ESLD over time. Conclusions: This study found that the majority of economic and wellbeing costs of NASH are experienced in late disease stages. Earlier diagnosis and care of NASH patients could reduce future healthcare costs.